Winchester Cathedral
Eight Norman columns of the south aisle arcade were carved in situ with the new perpendicular moldings, an operation which proved to be so laborious that later alteration work consisted of casing the piers with Caen stone, cut to the proper profiles. The height of the aisles was also increased during reconstruction.